Pernikahan dini ditinjau dari aspek hukum Islam dan ‎psikologi - Chaniago, Ikwal Pangsa (Maliki Interdisciplinary Journal, 2023)
Early marriage is a marriage carried out by children under 19 years of age. The current government does not provide a minimum ideal age for someone to get married. However, in Article 7 paragraph 1 is an article which is a rule that the minimum age for a person to marry between a man and a woman is at least 19 years. However, in Islam there is no minimum age requirement for marriage, regardless of age, you can perform the marriage service but must fulfill several conditions set by Islam, one of the conditions for marriage is the readiness of a person to marry. Our goal is to write this article to find out the legal basis for marriage here in Islam and some of the factors and impacts of early marriage. According to an Islamic perspective, marriage is a sunnah law and can change its law to become obligatory, mubah, makruh and even unlawful based on several factors and causes that make the marriage change its law. The phenomenon that occurs among our society today is the occurrence of pregnancy out of wedlock and the lack of supervision from parents towards our youth today. The environment of friendship and curiosity from teenagers so that they dissolve in the association without thinking about the consequences. The impact of early marriage can be seen from 3 aspects, namely physical aspects, cognitive aspects, and socio-emotional aspects.